Bee Poisoning - A Potential Threat to Biodiversity - Asritha, Chava; Satwika, M.; Rajashekhar, M.; Bharghavi, K.; Priyanka, N.; Keerthana, B.; Ramesha, N. M. (Chronicle of Bioresource Management, 2024)
Honeybees are valuable insects that are critical for pollinating many crops, contributing significantly to the global economy. Apart from producing wax and honey, their primary role is to pollinate crops, which is essential for the growth and survival of many plant species. However, honeybees face numerous challenges, including biotic and abiotic factors that threaten their existence. The most significant and pressing threat to their survival is the use of pesticides in agriculture, especially neonicotinoids. The widespread use of these pesticides is putting honeybees at risk by poisoning them and compromising their health. As a result, it is crucial to take action to reduce the use of pesticides and other harmful chemicals to ensure that honeybees can continue to thrive and play their vital role in the ecosystem.